Creative-Thinking Skills in Explanatory Writing Skills Viewed from Learning Behaviour: A Mixed Method Case Study - Palupi, Bening Sri; Subiyantoro, Slamet; Triyanto, Triyanto; Rukayah, Rukayah (International Journal of Emerging Technologies in Learning (iJET), 2020)
Creative thinking involves the activities of complex skills and cognitive abilities, personality factors and motivations, styles, strategies, and metacognitive skills. Therefore, creative-thinking skills can reflect the students’ personality considered as unique individuals. On the other hand, the effectiveness of education can be seen from teaching practices and class climate. The application of guided inquiry learning (GIL) and problem-based learning (PBL) models is one effort to improve the effectiveness of education. This research is a mixed-method case study that aims to describe the behaviour of groups of students, studying with GIL and PBL, with high, moderate, and low creative-thinking skills. The mixed-method analysis applied is a concurrent embedded strategy that combines primary data (qualitative) and secondary data (quantitative) to complement each other. The results showed that the application of the GIL and PBL models was proved to be effective for learning explanatory writing skills. In terms of the creative-thinking skills, the higher the students’ creative-thinking skills are, the higher their explanatory writing skills will be. Students who have high creative-thinking skills also exhibit prominent attitudes during the learning process, such as intensity of asking frequently with substantive questions on the subject matter and having good opinion and leadership skills.